2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16614
|View full text |Cite
|
Sign up to set email alerts
|

A Body Of Knowledge For The Construction Engineering And Management Discipline

Abstract: Many engineering professional associations and societies have defined the body of knowledge (BOK) related to their specific engineering disciplines to define the knowledge, skills, and attitudes necessary to become licensed and/or certified to practice professionally. Educators can use such BOKs to identify the knowledge domain for undergraduate and graduate degree programs. A construction engineering and management BOK has not been previously established. As part of a longitudinal review of the construction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In their study, Hildreth and Gehrig [13] identified the following four principal knowledge areas Step…”
Section: The Body Of Knowledge (Bok) For Cone Educationmentioning
confidence: 99%
“…In their study, Hildreth and Gehrig [13] identified the following four principal knowledge areas Step…”
Section: The Body Of Knowledge (Bok) For Cone Educationmentioning
confidence: 99%